Kinetic, Spectroscopic and Polarographic Determination of Trivalent Ions in an Imine System. - GAUR, SANTWANA; SHARMA, BEENA (Asian Journal of Chemistry, 2010)
Complexes of Al(IlI), Cr(IlI), Mn(III), Fe(III), Co(III) and Bi(III) with Schiff's base derived from the condensation of 2-oxo-1- benzopyran-3-carboxylic acid and o-aminothiophenol have been prepared. The kinetic parameters of decomposition have also been evaluated both by Freeman-Carroll and Sharp-Wentworth methods. D.C. electrical conductivity of the complexes has been studied. Differential pulse polarography has been chosen to follow the metal reduction process.